Dynamics of organizational change in the development of customary institutions: A Case Study of Keitemung Indigenous Organization Design - Waicang, Rode; Ibrahim, Akmal; Nara, Nurdin; Hasniati, Hasniati; Iskandar, Didik (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This research analyzes the contextualization of indigenous community identity and the adaptation process resulting from the establishment of Adat Villages in Jayapura Regency. Using a qualitative approach as a foundation, the study applies social identity theory in the case study of Keitemung Adat Village. Data were collected through observation, interviews, documentation studies, and Focus Group Discussions (FGD), involving 14 informants from various levels of government and the indigenous community. Data analysis was conducted through data reduction, presentation, conclusion drawing, and verification. The findings show that the social structure based on customary norms and cultural values plays a crucial role in maintaining community integration and stability. Effective leadership, the practice of mutual cooperation, and conflict resolution based on deliberation strengthen the role of cultural norms as coordination tools. Despite organizational changes due to government policies, cultural values continue to function as the main pillars, supporting social harmony and reinforcing collective identity within the cultural and social framework.